Effect of ion exchange resin particle size on homogeneity and leachability of Cs and Co in polymer waste form. Issue 5 (13th January 2021) - Kim, Jueun; Singh, Bhupendra Kumar; Um, Wooyong
Abstract : Ball mill ground IER waste form resulted in relatively better homogeneous waste distribution and displayed superior Cs leachability compared with the same polymer waste form prepared with non-ground IER. Abstract : We report the size effect of ion exchange resins (IERs) on Cs and Co distribution in polymer waste forms. Ball mill ground IERs (BG) waste form resulted in relatively better homogeneous waste distribution and displayed superior Cs and Co leachability indexes compared with the same polymer waste form prepared with non-ground IERs (NG).